Explaining evil - Ellens, J. Harold, 1932- (Psychology, religion, and spirituality., 2011)
What is evil? And what is the antidote to this universal malady, however it is defined? Traditionally, people have turned to religion when seeking a remedy to apparent evil. However, sociologists, psychologists, historians, philosophers, and even lawyers can also provide valuable insights in addressing the perplexing issue of evil.